Intermittent catheterisation with hydrophilic and non-hydrophilic urinary catheters: systematic literature review and meta-analyses - Rognoni, Carla (BMC Urol, 2017)
BACKGROUND: Intermittent catheterisation is the method of choice for the management of bladder dysfunctions. Different urinary catheters are available, but there is conflicting evidence on which type of catheter is best. The present study provides an objective evaluation of the clinical effectiveness of different subsets of urinary catheters. METHODS: A systematic literature review was performed for published RCTs regarding hydrophilic coated and PVC (standard) catheters for intermittent catheterisation. Separate meta-analyses were conducted to combine data on frequencies of urinary tract infections (UTIs) and haematuria. Two separate analyses were performed, including or excluding reused standard catheters. RESULTS: Seven studies were eligible for inclusion in the review. The meta-analyses exploring UTI frequencies showed a lower risk ratio associated with hydrophilic catheters in comparison to standard ones (RR = 0.84; 95% CI, 0.75–0.94; p = 0.003). Results for the “reuse” scenario were consistent with the ones related to “single-use” scenario in terms of frequency of UTIs. The meta-analyses exploring haematuria were not able to demonstrate any statistically significant difference between hydrophilic catheters in comparison to standard ones. CONCLUSIONS: The findings confirm previously reported benefits of hydrophilic catheters but a broader evaluation that takes into account also patient preferences, compliance of therapy, quality of life and costs would be needed to assess the economic sustainability of these advanced devices. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12894-016-0191-1) contains supplementary material, which is available to authorized users.